2008
DOI: 10.1182/blood-2007-06-093302
|View full text |Cite
|
Sign up to set email alerts
|

Development of an allele-specific minimal residual disease assay for patients with juvenile myelomonocytic leukemia

Abstract: Juvenile myelomonocytic leukemia is an aggressive and frequently lethal myeloproliferative disorder of childhood. Somatic mutations in NRAS, KRAS, or PTPN11 occur in 60% of cases. Monitoring disease status is difficult because of the lack of characteristic leukemic blasts at diagnosis. We designed a fluorescently based, allele-specific polymerase chain reaction assay called TaqMAMA to detect the most common RAS or PTPN11 mutations. We analyzed peripheral blood and/or bone marrow of 25 patients for levels of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…To this aim, we conducted a longitudinal monitoring of chronic myelomonocytic leukemia course first by sequencing and then by allele-specific PCR. In fact, among the various assays developed for early detection of specific mutations, tracking of disease progression, and evaluation of molecular response to therapy, which are crucial issues in clinical practice, allele-specific PCR represents a simple, fast, and sensitive method (35,36). Direct sequencing detected a significantly higher incidence of RAS mutations in MP-CMML patients, consistent with previous reports (1,5,(7)(8)(9)14).…”
Section: Discussionsupporting
confidence: 80%
“…To this aim, we conducted a longitudinal monitoring of chronic myelomonocytic leukemia course first by sequencing and then by allele-specific PCR. In fact, among the various assays developed for early detection of specific mutations, tracking of disease progression, and evaluation of molecular response to therapy, which are crucial issues in clinical practice, allele-specific PCR represents a simple, fast, and sensitive method (35,36). Direct sequencing detected a significantly higher incidence of RAS mutations in MP-CMML patients, consistent with previous reports (1,5,(7)(8)(9)14).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, novel methods of detecting relapse early post-transplant beyond traditional donor chimerism include sorted cell donor chimerism, quantitative PCR to assess chimerism, as well as allele-specific PCR strategies to detect mutation-specific clones. 42,46 Such sensitive measurements may facilitate earlier and more rapid withdrawal of immunosuppression or the initiation of novel targeted therapies. There are minimal data on the utility of donor lymphocyte infusions.…”
Section: Approaches To Hsctmentioning
confidence: 99%
“…41 In addition to such criteria, allele-specific, polymerase chain reaction (PCR)-based strategies have been developed to track specific mutations in patients on therapy and will be tested in future clinical trials to determine their role prospectively. 42 Future targeted therapies are being intensely investigated in a variety of laboratories around the country. Such potential therapies include Janus kinase (JAK) inhibitors, based on work demonstrating a pSTAT5 response in JMML cells upon exposure to subtherapeutic concentrations of GM-CSF, 43 as well as other signal transduction components of Ras signaling, such as PI3K (phosphoinositide 3-kinase), MEK (MAPK/extracellular-signal-regulated kinase [ERK] kinase), and mTOR (mammalian target of rapamycin) inhibitors.…”
Section: Approaches To Therapy Prior To Hsctmentioning
confidence: 99%
“…Using this method, the authors demonstrated the possibility to quantify disease burden before HSCT and to measure minimal residual disease after HSCT in JMML patients. 12 In this context, upon confirmation and extension in larger series, flow cytometric monitoring of STAT5 phosphorylation signature may also represent a rapid and sensitive tool to evaluate response to therapy even in those patients without PTPN11 and RAS mutations.…”
mentioning
confidence: 99%